Flow visualization and mechanisms of three-electrode sliding discharge plasma actuator. (October 2019) - Zheng, Borui; Chen, Jie; Ge, Chang; Ke, Xizheng; Liang, Hua
The unsteady flow characteristics induced by a three-electrode sliding discharge plasma actuator under different actuation modes were analyzed by ensemble averaged and phase-locked particle image velocimetry. The discharge morphologies, voltage–current waveforms, and particle image velocimetry data in continuous mode were compared to clarify the performance modification mechanism of the pulsed three-electrode sliding discharge. The particle image velocimetry results revealed that deformation of the electromagnetic field around the additional electrode caused by applying a high DC voltage triggers changes in the induced flow field. When the three-electrode sliding discharge plasma actuator is actuated in continuous mode, a strong accelerated wall jet and homogeneous discharge region covering the whole gap between the two exposed electrodes are generated. The large discharge extension mainly results from the accelerated drift of positive ion particles created during the positive half cycle, while negatively ionized particles have a significantly larger impact on the induced velocity production process. In the pulsed mode, when a positive high DC voltage ( V DC = 18 kV) is applied to the additional electrode, both the size and magnitude of the induced vortex structures increase, and highly accelerated regions are periodically generated. When V DC = −18 kV, the induced velocity field evens out, the accelerated region becomes less obvious, the intensity of both the primary and secondary vortices decreases, and the vortex structure dissipates faster, owing to the turbulent motion of ionized particles. An additional positive DC component attracts the negatively ionized particles during the negative half cycle, improving the velocity and intensity of the stream-wise vortices, which is very attractive for flow control applications.